KAJIAN PERUBAHAN PENGGUNAAN LAHAN TERHADAP LAJU EROSI PERMUKAAN DI DAERAH TANGKAPAN AIR WADUK MRICA - Hanafi, Fahrudin (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2015)
Surface erosion is one of the determining variable of critical watershed, this related to river basin managementwhich always prioritized to critical land . Along with land use changes that lower watershed function, theassessment of land use change on surface erosion becomes very important. The research was conducted oncatchment of Mrica reservoir, especially in Serayu, Merawu, Lumajang, and Liangan. The data input of land usechanges are from 2001-2009 that using Landsat TM and ALOS. The soil loss calculating method is MUSLE(Modified Universal Soil Loss Equation). DEM data as a function of slope can be used to analyze at pixel level ofaccuracy,soil data as erodibility function, and discharge as erosivity function. Musle analysis results indicatethat the average surface erosion of Mrica reservoir catchment are 16,775,896 tons per year or 11,183,931 m3 peryear, equivalent to the soil loss thickness as 16:13 mm per year. Result of land use changes effect to surfaceerosion in the research area are moor, plantations, and scrub with R :0.85 positive correlation; 0.84, and 0.86.Forest, correlates negatively to the surface erosion with R coefficient: 0.88. Thus, managing land use with highcorrelation coefficient will greater impact to suppress soil loss/ erosion.